2018
DOI: 10.14311/app.2018.14.0027
|View full text |Cite
|
Sign up to set email alerts
|

Neutronic Analysis of the Candidate Multi-Layer Cladding Materials With Enhanced Accident Tolerance for Wwer Reactors

Abstract: Abstract. The paper summarizes preliminary results of neutronic analysis of candidate ATF cladding materials that are under development at the CTU in Prague. To evaluate basic neutronics-related characteristics the Serpent code was used which is a Monte-Carlo based simulation tool. A model of WWER fuel was developed and basic neutronic analysis performed. All coating materials entail certain reactivity penalty compared to reference uncoated cladding that was quantified. The coating of cladding affects also oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The calculations also showed that metallic chromium had more stopping power and less total induced displacement damage in comparison with the Zr-based alloy. It is worth mentioning that, the calculated minimum thickness of Cr is not expected to significantly affect the reactor reactivity and would probably results in less than a 1% decrease in fuel cycle length according to calculations made by Novak and Sevecek [21]. On the other hand, applying an inner surface thin film will provide protection for the fuel cladding against the internal corrosion and SCC, supporting the ability to increase fuel burnup during reactor operation as well as contributing to improved spent fuel management and waste minimization.…”
Section: Discussionmentioning
confidence: 84%
“…The calculations also showed that metallic chromium had more stopping power and less total induced displacement damage in comparison with the Zr-based alloy. It is worth mentioning that, the calculated minimum thickness of Cr is not expected to significantly affect the reactor reactivity and would probably results in less than a 1% decrease in fuel cycle length according to calculations made by Novak and Sevecek [21]. On the other hand, applying an inner surface thin film will provide protection for the fuel cladding against the internal corrosion and SCC, supporting the ability to increase fuel burnup during reactor operation as well as contributing to improved spent fuel management and waste minimization.…”
Section: Discussionmentioning
confidence: 84%
“…However, the thickness of protective coatings on Zr-based claddings should be limited to avoid a significant impact on the neutron transport in LWRs. For example, for Cr coatings, thickness should not exceed 30 µm, so that the reduction of fuel cycle life would be limited to 1% [167].…”
Section: Microstructure and Thickness Of The Coatingsmentioning
confidence: 99%
“…Coating slows down the absorption rate of hydrogen as well as the process of oxidation in normal operation [4][5][6]. Moreover, calculations show that a thin layer of Cr entails only a minor decrease in a fuel cycle length [7]. Regarding the accident conditions, the positive impact of Cr coating has been presented.…”
Section: Introductionmentioning
confidence: 99%